The Role of Nahdlatul Ulama in Strategizing Vaccine Communication during Covid-19 - Naura Safira Salsabila Zain; Haekal Adha Al Giffari; Abda Kamalia Putri (Departement of Comparative Study of Religions, 2022)
Nahdlatul Ulama, as the biggest Islamic civil society in Indonesia, has a significant contribution in managing the risks of the pandemic in Indonesia as Covid-19 affects adversely against Indonesian. The issue of Covid-19 and its development always ignites the debate in Indonesia, including the vaccination process to minimize the virus risks. A plethora of rumours related to vaccination is spreading widely among Indonesian society which is more likely leading to adverse attitudes and behaviour of the people against vaccination. This research will elaborate on the role of Nahdatul Ulama in managing public risk communication about vaccination. The Public Risk Communication concept will be used in this research as the main framework. Library studies and document analysis are employed in this research to explore related data and information. The data will be analyzed based on the framework suggested. The result shows that Nahdatul Ulama has sufficient public risk communication management as it fulfils the framework suggested in delivering the information about vaccination to penetrate the messages in a subtle way. In conclusion, Nahdlatul Ulama has a systematic public risk communication management in delivering the messages about vaccination for most Indonesians.